When Vision Becomes a Voice on the Line – Assistive Technologies in the Daily Lives of Blind People, the Innovative Be My Eyes for Visual Assistance - Stojkow, Maria; Trela, Laura (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Assistive technologies play a pivotal role in the lives of people living with disabilities, enhancingtheir autonomy and facilitating their day-to-day functioning. Tis article focuses on an analysisof the Be My Eyes app, which provides remote visual assistance by connecting blind and partiallysighted individuals with volunteers. A qualitative study, grounded in in-depth interviews, wasconducted to identify users’ primary motivations for utilising the app, their experiences, and theimpact of technology on their sense of independence. Te role of artifcial intelligence in visual assistanceand the users’ interaction with volunteers has also been given particular attention. Te resultsof the study indicate that Be My Eyes is not only a practical tool to support daily activities, butalso an important element infuencing users’ psychological comfort and sense of independence.